Development of a novel vector for siRNA delivery based on arginine‐modified polyvinylamine. Issue 8 (16th March 2022) - Lin, Mei; Lin, Aizhu; Huang, Sheng; Liu, Tianhui; Ke, Fang; Qiu, Deshun; Lin, Xuefeng; Luo, Daoshu
Abstract: An ideal carrier that delivers small interfering RNA (siRNA) should be designed based on two criteria: high gene transfection efficiency and low cytotoxicity. In this work, arginine was used to modify polyvinylamine (PVAm) to form a novel PVAm derivative (PVAm‐Arg) for siRNA delivery and the derivative was characterized using Fourier transform infrared spectroscopy. PVAm‐Arg/siRNA complexes were formed by the self‐assembly method. The zeta potential and size of the complexes were measured using electrophoretic light scattering and dynamic light scattering, respectively. The siRNA binding capacity of PVAm‐Arg was assessed using gel retardation assay. The results showed that PVAm‐Arg derivatives can bind siRNA effectively and form complexes with sizes of about 72 ± 2 nm. What is more, the ability of PVAm‐Arg to condense siRNA was better than that of PVAm. Cytotoxicity assay with RSC96 cells also showed that PVAm‐Arg had lower cytotoxicity compared with PVAm. In in vitro cellular uptake assay, PVAm‐Arg showed good transfection efficiency. Therefore, we concluded that PVAm‐Arg would be a promising candidate as a gene delivery vector. © 2022 Society of Industrial Chemistry. Abstract : A novel polymer based on arginine‐modified polyvinylamine (PVAm‐Arg) was synthesized. Its structure was measured and its performances as a gene delivery carrier was investigated.